Determination of optimum stocking density of catfish (Clarias macrocephalus Ganther) eggs during incubation. - Jardeleza, Maria Stephanie Ravadilla
Clarias macrocephalus (Gunther), a native catfish in the Philippines, is rapidly vanishing species that attempts at induced breeding have been made involving administration of hormones. To maximize the cost and effort of preparation for fertilization and hatching of catfish eggs, the optimum number of eggs placed in the incubator should be determined. Three egg stocking densities (1000 eggs/1,2000 eggs/1, and 4000 eggs/1) were tested in this study to determine optimum stocking density for improvement of hatching efficiency. Eggs were left at ambient temperature to hatch until 24-30 hours after incubation. Dissolved oxygen (DO), pH, temperature, and ammonia-nitrogen (NH3-N) were taken at 0, 12, and 24 hour post-incubation., No significant differences (p>0.05) were found to exist among the different stocking densities in terms of percent egg viability and percent hatching. However, this does not indicate the absence of a relationship between percent hatching and stocking density. Mean percent hatching was found to decrease as stocking density increased, although not significantly. No such trend was observed with mean percent viability. High egg mortalities were attributed to mechanical shock, oxygen deprivation, egg (fungal) infection, parasitic infestation, and water pollution from metabolic waste accumulation. Water parameters remained within the optimum ranges for incubation and hence were not limiting factors. DO decreased while pH and NH3 increased significantly (p<0.01) as development entered gastrulation (12 hr post-incubation). DO and pH decreased, while NH3 content increased significantly (p>0.05) as stocking density increased. Based on the present study, a stocking density of up to 4000 eggs/1 may be used during catfish incubation, although the ceiling stocking density should be determined in future incubation experiments. (NOTE: correction NH3)